Reducing image search time by improved BOVW with wavelet decomposition - Mohammed El Amin Kourtiche; Mohammed Beladgham; Abdelmalik Taleb-Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In the last decade, the bag of visual words (BOVW) has been used widely in image classification, image retrieval and has significantly improved the performance of CBIR system. In this paper we propose a new method to enhance BOVW using features obtained from wavelet decomposition in order to reduce computational costs in vocabulary construction and training time. We apply several level of wavelet decompositions and evaluate their impact on accuracy of the BOVW. We apply our method on MURA-v1.1 dataset and the experiments results confirm the performance of our approach.